Study On Heart Rate Visualisation Using Combination Of Real Time Heart Rate Detection And Augmented Reality - Mohammed, Norazlin; Idrus, Junaidah (Indian Journal of Public Health Research and Development, 2019)
Heartbeat is a natural process which the heart continuously beating without any control from the living thing while heart rate is the speed of the heartbeat measured by the number of contractions of the heart per minute (BPM). There are few methods that can be used to check heart rate. Traditionally, heart rate is check by placing a finger on wrist or temple area and the pulse is counted in one minute. There are few devices that can be used to check the heart rate such as a stethoscope, electrocardiogram (ECG) and chest strap. This paper presents the study on the comparison of these devices that are commonly used nowadays. As analysis being done, none of the existing devices provide visualization features that enable user to see how the heart beating process happen in a human’s body. This paper also presents the study on providing visualization of heart beating process by using Augmented Reality in delivering health information to improve the understanding on user heart condition whiles getting their real-time heart rate. Since AR is one of the new emerging technologies, it can be used to visualize the user heart beat in real time and user can interact with the application to get details of their heart condition. This project also aimed to encourage the user to do frequent heart rate checkup in order to let them monitor their health by providing interactive features of ‘Lean Touch’ where heart model can be scaled, moved, and zoomed